2017
DOI: 10.4103/jovr.jovr_20_17
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of various intraocular lens power calculation formulas in steep corneas

Abstract: Purpose:To compare the accuracy of four different intraocular lens (IOL) power calculation formulas for eyes with mean keratometry values greater than 46 diopters (D).Methods:Forty five eyes from 45 patients who were candidates for senile cataract surgery with mean keratometry values greater than 46 D were included. Calculation of the IOL power was performed by the Lenstar. The implanted IOL in all cases was Acrysof SA60AT. The average absolute value of the differences between the actual and predicted spherica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Using the Mann-Whitney U-test, it was found that there was no significant difference between the SRK/T and Haigis formulas in predicting the accuracy result of the ME. This is in line with research conducted by Faramarzi et al which stated that in eyes with steep corneas, statistically, it showed no significant difference between the accuracy of the four formulas (Haigis, Holladay 1, Hofer-Q, SRK/T), and general IOL power calculations [14]. This is not in line with the research conducted by Sharma et al where the research compared the prediction accuracy of the SRK/T and Haigis formulas without optimized constants where the SRK/T formula was in ± 1.00 D and ± 2.00 D which were 78% and 96%, while in the Haigis formula, without personal constants within ± 1.00 D and ± 2.00 D were 86% and 100%, where the Haigis formula was significantly more precised than the SRK/T formula [15].…”
Section: Discussionsupporting
confidence: 91%
“…Using the Mann-Whitney U-test, it was found that there was no significant difference between the SRK/T and Haigis formulas in predicting the accuracy result of the ME. This is in line with research conducted by Faramarzi et al which stated that in eyes with steep corneas, statistically, it showed no significant difference between the accuracy of the four formulas (Haigis, Holladay 1, Hofer-Q, SRK/T), and general IOL power calculations [14]. This is not in line with the research conducted by Sharma et al where the research compared the prediction accuracy of the SRK/T and Haigis formulas without optimized constants where the SRK/T formula was in ± 1.00 D and ± 2.00 D which were 78% and 96%, while in the Haigis formula, without personal constants within ± 1.00 D and ± 2.00 D were 86% and 100%, where the Haigis formula was significantly more precised than the SRK/T formula [15].…”
Section: Discussionsupporting
confidence: 91%
“…Olsen et al [ 10 ] found a significant negative correlation of the prediction error with the keratometric readings (r = -0.23, p<0.0001), when the SRK/T formula was used. Faramarzi et al [ 13 ] demonstrated that the prediction error was -0.06 ± 0.52 D in eyes with a keratometry > 46 D, when the SRK/T formula was applied. Reitblat et al [ 14 ] showed that myopic refractive errors (-0.31 ± 0.54 D) were found in eyes with a keratometry > 46 D, but hyperopic errors (0.16 ± 0.31 D) were observed in eyes with a keratometry < 42 D, when the SRK/T formula was used, and that the prediction error was -0.04 ± 0.45 D and -0.07 ± 0.26 D, in eyes with a keratometry > 46 D and < 42 D, respectively, both of which were not significantly different from zero, when the Barrett Universal II formula was used.…”
Section: Discussionmentioning
confidence: 99%
“…Olsen et al [8] found a significant negative correlation of the prediction error with the keratometric readings (r � −0.23, p < 0.0001), when the SRK/T formula was used. Faramarzi et al [9] demonstrated that the prediction error was −0.06 ± 0.52 D in eyes with a keratometry >46 D using the SRK/T formula, but that the sample size was limited (n � 45). Reitblat et al [10] showed that myopic refractive errors (−0.31 ± 0.54 D) were found in eyes with a keratometry >46 D, but hyperopic errors (0.16 ± 0.31 D) were noted in eyes with a keratometry <42 D, when the SRK/T formula was used, and that the prediction error was −0.04 ± 0.45 D and −0.07 ± 0.26 D, in eyes with a keratometry >46 D and <42 D, respectively, both of which were not significantly different from zero, when the Barrett Universal II formula was used.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, there have only been a few studies on the predictability of the IOL power calculation using the two major formulas, according to the keratometric readings [8][9][10]. Moreover, the detailed relationship between the predictability outcomes and the keratometry has so far not been elucidated using the two major formulas.…”
Section: Introductionmentioning
confidence: 99%